2018
DOI: 10.4209/aaqr.2016.11.0493
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Bacterial Community in Size-Resolved Cloud Water at the Summit of Mt. Tai, China

Abstract: A three-stage collector was used to collect size-resolved cloud samples at the summit of Mt. Tai. Subsequently, analyses of pH values, water-soluble ions, and trace metals were performed and bacterial community were conducted using MiSeq amplicon sequencing. The pH values of the samples decreased as droplet sizes decreased. Sulfate (SO 4 2-), nitrate (NO 3 -) and ammonium (NH 4 + ) were the main secondary inorganic ions which their concentration distributed significantly different from size-resolved cloud wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
(66 reference statements)
2
7
0
Order By: Relevance
“…Clouds and snow generally had the highest diversity in both bacterial and fungal datasets, with atmosphere and rain being the least diverse. Cloud bacterial communities were dominated by Proteobacteria, Actinobacteria and Bacteriodetes, which has also been observed in several cloud water studies from China, France, southern Africa and the USA (Jiaxian et al 2019;Amato et al 2017;Kourtev et al 2011;Zhu et al 2018;Evans et al 2019). Fifteen of overall identified fungal genera were unique to clouds, whereas only 9% of bacterial genera were unique to clouds.…”
Section: Comparison Of Community Structure and Abundance In Air And Psupporting
confidence: 72%
See 1 more Smart Citation
“…Clouds and snow generally had the highest diversity in both bacterial and fungal datasets, with atmosphere and rain being the least diverse. Cloud bacterial communities were dominated by Proteobacteria, Actinobacteria and Bacteriodetes, which has also been observed in several cloud water studies from China, France, southern Africa and the USA (Jiaxian et al 2019;Amato et al 2017;Kourtev et al 2011;Zhu et al 2018;Evans et al 2019). Fifteen of overall identified fungal genera were unique to clouds, whereas only 9% of bacterial genera were unique to clouds.…”
Section: Comparison Of Community Structure and Abundance In Air And Psupporting
confidence: 72%
“…and Mg 2? (Jiaxian et al 2019), which main sources are soil dust in big cloud droplets (Zhu et al 2018). Janthinobacterium has antifungal properties (Rubio et al 2018) and was found in high mountain lakes and Antarctica (Ahern et al 2007) and alpine cryoconite, and is known for its psychrotolerant properties (Kim et al 2012).…”
Section: 8mentioning
confidence: 99%
“…Tai is far away from anthropogenic emission sources on the ground. However, high concentrations of inorganic ions in PM 2.5 (Zhou et al, 2009), abundant bacterial communities (Zhu et al, 2018), and NH 3 and NO x emissions from biomass burning (Chang et al, 2019a) have been observed at the summit, and thus a strong anthropogenic influence must exist. Previous studies of cloud samples collected at the same position showed high inorganic ion concentrations (J.…”
Section: Introductionmentioning
confidence: 99%
“…Particles of biological origin are ubiquitous in the atmosphere. , Diverse live, culturable microorganisms have been isolated from clouds and atmospheric aerosol samples. Typical phyla include Proteobacteria (especially Pseudomonas syringae , which is an effective ice nucleating agent), Bacteroidetes, Cyanobacteria, and Firmicutes. rDNA/rRNA sequencing of microbes collected in clouds and aerosols at mountaintop locations has provided evidence for metabolically active cells in these atmospheric samples.…”
Section: Introductionmentioning
confidence: 99%